Works Councils, Quits and Dismissals in Germany - Christian Grund; Andreas Helmut Schmitt (Institute for the Study of Labor (IZA), 2013)
We examine the relationship between works councils and two different types of employment separation: dismissals by the firm and voluntary quits by employees. Based on representative data from the German Socio-Economic Panel, we find a negative relationship between works councils and both kinds of separation. This is particularly true for skilled blue collar as well as qualified white collar workers compared to employees in other job categories. Additionally, we find first hints for a positive relation between works councils and the relevance of severance payments in the case of dismissals.
Keywords: M5; J6; 330; dismissal; employment separation; quit; severance pay; works council